Utilisation of 2,2DCP by Staphyloccocus aureus ZT and In Silico Analysis of Putative Dehalogenase - Zaidi, Zatty Zawani; Huyop, Fahrul (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Halogenated compound such as 2,2-dichloropropionic acid is known for its toxicity and polluted many areas especially with agricultural activities. This study focused on the isolation and characterization of the bacterium that can utilise 2,2-dichloropropionic acid from palm oil plantation in Lenga, Johor and in silico analysis of putative dehalogenase obtained from NCBI database of the same genus and species. The bacterium was isolated using an enrichment culture media supplemented with 20 mM 2,2-dicholoropropionic acid as a carbon source. The cells were grown at 30˚C with cells doubling time of 2.00±0.005 hours with the maximum growth at A680nm of 1.047 overnight. The partial biochemical tests and morphological examination concluded that the bacterium belongs to the genus Staphylococcus sp.. This is the first reported studies of Staphylococcus sp. with the ability to grow on 2,2-dichloropropionic acid. The genomic DNA from NCBI database of the same species was analysed assuming the same genus and has identical genomic sequence. The full genome of Staphylococcus sp. was screened for dehalogenase gene and haloacid dehalogenase gene was detected in the mobile genetic element of the species revealed that the dehalogenase sequence has little identities to the previously reported dehalogenases.The main outcome of the studies suggesting an in situ bioremediation can be regarded as a natural process to detoxify the contaminated sites provided that the microorganisms contained a specialised gene sequence within its genome that served the nature for many long years. Whether microorganisms will be successful in destroying man-made contaminants entirely rely on what types of organisms play a role in in situ bioremediation and which contaminants are most susceptible to bioremediation.